Money Isn't Everything : The Challenge of Scaling Up Aid to Achieve the Millennium Development Goals in Ethiopia - Mattina, Todd (IMF Working Papers; Working Paper, 2006)
This paper outlines the challenge of developing an operational macroeconomic framework in Ethiopia consistent with the large envisaged scaling up of aid to achieve the Millennium Development Goals (MDGs). This paper describes an MDG scenario that addresses both microeconomic and macroeconomic constraints, such as the need to boost sustainable growth, limit Dutch disease, formulate an exit strategy from aid dependency, enhance public financial management (PFM), and expand the supply of skilled labor. The paper will argue that a carefully sequenced MDG strategy is essential so that the scaled-up aid and public spending will remain in line with Ethiopia's absorptive capacity.